A Dampak Model Learning Cycle Terhadap Pemahaman Konsep Momentum dan Impuls - Rizka Putri Handayani; Abdul Halim; Ngadimin; Abdul Hamid; Fitria Herliana (Postgraduate, University of Mataram, 2024)
This study aims to determine the impact of the Cycle Learning model toward understanding the concept of momentum and impulse. The study used a quantitative approach, quasi-experimental methods and a non-equivalent pretest-posttest control group design in two classes of high school students as the research sample. Data collection was carried out using a physics concept understanding test (PCUT) and data analysis using the t-test at a significance level of 0.05 to find out the difference between the control class and the experimental class. The results of the data analysis show that: The Learning Cycle 7e model has an effect on increasing understanding of concepts. The 7E Learning Cycle model is better than conventional techniques from the aspect of increasing understanding of concepts. The level of conceptual understanding through the Learning Cycle 7e model is obtained by the level of complete understanding (LCU), while conventional techniques are only obtained by the level of partial understanding (LPU). The application of the Learning Cycle 7e learning model in learning is proven to be able to influence students' conceptual understanding skills for the better.